Creation Of Event Enlightenment Networks Based On Intercultural Dialogue Of Peoples Of Different Countries - Якушкина, Марина (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The necessity of learning new educational process participants different age’s communities (eventual community) created by children, youth, adults (parents, teachers, scientists, politicians, etc.) at cultural and educational forums through formally planned events, through educational events and daily co-existence is analyzed. The purpose of the research: it is substantiated that the designing event enlightenment networks using the Russian language as a language of communication through intercultural dialogue of different age’s communities. Results: it is proved that the development of education of different age’s communities requires reformatting the sphere of enlightenment related to updating non-formal (self-education), increasing information network resources, delimiting humanitarian educational activities and activities with destructive value orientations, strengthening the relationship of education, socialization, upbringing, development, human education.